CONTINUOUS PIGGERY WASTEWATER TREATMENT WITH ANAEROBIC BAFFLED REACTOR (ABR) BY BIO-ACTIVATOR EFFECTIVE MICROORGANISMS (EM4) - I Wayan Koko Suryawan; Gita Prajati; Anshah Silmi Afifah; Muhammad Rizki Apritama; Yosef Adicita (Universitas Trisakti, 2019)
Aim: The purpose of this study was to determine the efficiency and characteristics of pig wastewater treatment. This was to be achieved using ABR with the addition of effective microorganism4 (EM4) as a bio-activator during the startup process (R1) and without EM4 (R2). Methodology and Results: Piggery wastewater is poured into ABR with 12 hours HRT (hydraulic retention time), though it is reduced to 6 hours after the concentration is stable. The COD removal efficiency at 12 hours HRT was 60% (R1) and 51% (R2). However, the results did not change significantly, since the 6 hours HRT COD efficiency was 57.8% (R1) and 51.3% (R2). The biomass growth rate at R1 is faster than R2 with Food to Microorganism Ratio (F/M) 0.4-0.89 (R1) and 0.68-1.38 (R2) while the yield of methane gas formation was 0.25-0.28 L-CH4/g-COD. Conclusion, significance, and impact study: COD effluent is the total organic material present in the piggery wastewater effluent, which is discharged into water bodies without meeting the set quality standards. This damages the quality of water bodies. The wastewater treatment needs to be prioritized to meet quality standards of COD effluent. Also, the addition of EM4 to the activated sludge reactor improves the COD removal efficiency and biomass growth, though advanced treatment is still needed for piggery wastewater.